The impact of celebrity endorsement towards metrosexual men buying behaviour for facial skincare products in Kuala Lumpur, Malaysia / Syamil Izzan Alfansu - Alfansu, Syamil Izzan (2016)
Since recent years celebrities are being contracted increasingly by companies in order to endorse their products and brand (Kamins & Gupta, 1994). The fact is that celebrities endorsers have become an important feature of modem marketing, which is present everywhere (McCracken, 1989). In this study the based on the dimensions of the Celebrity Endorsement itself which are celebrity attractiveness, celebrity credibility and celebrity audience match up and the relationship with the buying behaviour of metrosexual men towards facial skin care products will be investigated. The impact of these dimensions towards the buying behaviour of metrosexual men for facial skincare products will also be analysed. The location of this study will be at Kuala Lumpur, Malaysia so the result will not be generalized. This research will be using frequency statistics, descriptive analysis, reliability analysis, multiple regression analysis and Pearson’s correlation analysis in answering the objective of the research. Recommendations will be made based on the findings.